Improving soft magnetic properties in FINEMET-like alloys. A study - Moya, Javier Alberto (2014)
An approach to improve the soft magnetic properties of nanocomposite FINEMET-like alloys is presented by the study of the theoretical behavior of the coercive field with the crystallized fraction, Hc(mcr), curves where the total anisotropy is taken into account. These curves can exhibit a minimum value that should be used for a proper design of soft magnetic alloys, consisting in matching that value with the optimal crystallized fraction of the alloy. For this, the effect of Si, Ge, Co and Al on the magnetic properties on the material phases and on its microstructure was analyzed while a good relationship between theoretical results and data in the literature was found. Small amounts of Ge and/or Al can improve the magnetic properties of FINEMET while the addition of Co deteriorates the coercive field as is predicted by the theory. Simultaneous addition of two or more solute elements to the a-Fe crystals was also evaluated and discussed. Results indicate the importance of knowing the effect of the alloying element on the crystalline magnetostriction constant and on the crystallized fraction of the microstructure.